Feeding patterns in relation to malocclusions due to thumbsucking - Arvisu, Margaret M.; Cayco, Mirabel; Sanatayana, Crisanta C. (Adviser).
A study was conducted to determine the incidence of thumbsucking among 500 selected grade 2 pupils in relation to their feeding pattern using individual questionnaires. Results showed that from the 134 children that were bottle-fed, 34 (25.54%) had a history of the thumbsucking habit. Out of the 140 mixed-fed babies, 34 (24.29%) presented with a history of the habit and of the 40 predominantly breast-fed babies, 14 (35.0%) had the habit. A similar study was made to determine whether the incidence among 14 orthodontic patients with malocclusions due to thumbsucking habits were influenced by a particular feeding method and weaning to the cup before the age of 1. Results showed that 5 (35.71%) of the 14 subjects were predominantly breast-fed and weaned to the cup before the age of 1. 4 (28.57%) were breast-fed and weaned to the cup after the age of 1. Only 1 was predominantly bottle-fed and weaned to the cup after the age of 1 or 7.14%. And 4 (28.57%), were mixed-fed babies were weaned to the cup after the age of 1. None of the subjects were predominantly bottle-fed and mixed-fed and were weaned to the cup before the age of 1.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Thumb sucking -- Physiological effects; Malocclusion in children